The interaction between N, P in the overlying water of the reservoir Water-level fluctuation zone and submerged decomposition of Cynodon dactylon - Huang, Jitao; Luo, Ze; Jiang, Yanxue (E3S web of conferences, 2024)
During the process of inundation in the Water-level fluctuation zone(WLFZ), the N and P content in the overlying water will vary due to the release of soil nutrients, directly impacting the decomposition process of plants. However, current research on the effects of such water changes on plant decomposition is insufficient, hindering an accurate assessment of its impact on water environments. This study simulated changes in water quality during inundation and designed 8 types of water with different initial nutrient levels. Taking the typical WLFZ plant, Cynodon dactylon, as the subject, the decomposition and dynamic changes of N and P in these water bodies were studied. The results showed that inundation significantly increased the N and P content in the water, and the initial forms of N and P significantly affected the release of plant decomposition during inundation. Moreover, the release of PN and PP from the soil stimulated the activity of aquatic microorganisms, enhancing the self-purification capacity of the water body, and leading to a decrease in N and P content in the water body after 60 days of inundation. This study reveals the impact of N and P released from WLFZ soil on plant decomposition and the concentrations of N and P in the overlying water. providing critical insights into WLFZ ecosystem management.